Camidanlumab tesirine in patients with relapsed or refractory lymphoma: a phase 1, open-label, multicentre, dose-escalation, dose-expansion study. Issue 6 (June 2021) - Hamadani, Mehdi; Collins, Graham P; Caimi, Paolo F; Samaniego, Felipe; Spira, Alexander; Davies, Andrew; Radford, John; Menne, Tobias; Karnad, Anand; Zain, Jasmine M; Fields, Paul; Havenith, Karin; et al.
Summary: Background: Novel approaches are required to improve outcomes in relapsed or refractory classical Hodgkin lymphoma and non-Hodgkin lymphoma. We aimed to evaluate camidanlumab tesirine, an anti-CD25 antibody–drug conjugate, in this patient population. Methods: This was a phase 1, dose-escalation (part 1), dose-expansion (part 2), multicentre trial done in 12 hospital sites (seven in the USA and five in the UK). Adults (≥18 years old) with pathologically confirmed relapsed or refractory classical Hodgkin lymphoma or non-Hodgkin lymphoma, an Eastern Cooperative Oncology Group performance status 0–2, who had no therapies available to them with established clinical benefit for their disease stage were enrolled. Camidanlumab tesirine was administered intravenously (3–150 μg/kg) once every 3 weeks. Primary objectives were to assess dose-limiting toxicity, determine maximum tolerated dose and recommended expansion dose(s), and assess safety of camidanlumab tesirine. Safety was assessed in all treated patients; antitumour activity was assessed in patients with one or more valid baseline and post-baseline disease assessment and in those who had disease progression or died after first study-drug dose. This trial was registered with ClinicalTrials.gov, NCT02432235 . Findings: Between Oct 5, 2015, and Jun 30, 2019, 133 patients were enrolled (77 [58%] had classical Hodgkin lymphoma and 56 (42%) had non-Hodgkin lymphoma). Median follow-up was 9·2 months (IQR 4·2–14·3). Eight dose-limiting toxicities were reported in five (6%) of 86 patients who were evaluable; the maximum tolerated dose was not reached. The recommended doses for expansion were 30 μg/kg and 45 μg/kg for patients with classical Hodgkin lymphoma and 80 μg/kg for patients with T-cell non-Hodgkin lymphomas. No recommended doses for expansion were defined for B-cell non-Hodgkin lymphomas. Grade 3 or worse treatment-emergent adverse events (reported by ≥10% of the 133 patients) included increased γ-glutamyltransferase (20 [15%] patients), maculopapular rash (16 [12%]), and anaemia (15 [11%]); 74 (56%) patients had serious treatment-emergent adverse events, most commonly pyrexia (16 [12%]). One (1%) fatal treatment-emergent adverse event and two (2%) deaths outside the reporting period were considered at least possibly study-drug related. Antitumoural activity was seen in classical Hodgkin and non-Hodgkin lymphomas; notably in all patients with classical Hodgkin lymphoma, the overall response was 71% (95% CI 60–81). Interpretation: These results warrant evaluation of camidanlumab tesirine as a potential treatment option for relapsed or refractory lymphoma, particularly in patients with classical Hodgkin lymphoma. Funding: ADC Therapeutics.